Improving Students’ Reading Comprehension Ability through School Literacy Movement - Setyorini, Metyana; Sayit Abdul Karim; Sudiro, Suryo (Loquen, 2023)
The establishment of the School Literacy Movement (Gerakan Literasi Sekolah-GLS) proposed by the authority at the Senior High School level is to tackle students’ reading skills problems, especially reading comprehension. The present study attempts to figure out students’ ability in reading comprehension and to describe factors influencing students’ ability in reading comprehension through the literacy program at SMA N 1 Bantul. True experimental pretest-posttest control group design was applied in the present study. Furthermore, a pre-test and post-test were conducted to obtain quantitative data from both the experimental and control groups. Meanwhile, a questionnaire with a Likert scale ranging from SA=4 to SD=1 was used to obtain data about factors influencing students’ ability in reading comprehension. The findings revealed that the literacy program improved students’ reading comprehension scores of the experimental group with an average score of 90.91, thus, this achievement is classified into the "Good" category. Meanwhile, the influencing factors namely internal and external factors, including readers' motivation and interest, as well as the external factors including reading materials, teachers, and questioning strategies. The results of this study may help teachers choose effective learning strategies to improve student's reading comprehension through literacy programs in years to come.